Rhabdomyolysis in a pregnant woman: A case report - Al-Hajjaj, Maher; Alabdaly, Abdilya Riyadh; Alqralleh, Muna; Juma Ibrahim, Dana Issa; Mohamed, Amna Elrayah (Clinical Journal of Obstetrics and Gynecology, 2023)
Hyperemesis gravidarum may prompt hypovolemia and significant electrolyte anomalies. Hypokalemia is one of the most common abnormalities. When practical, it may lead to rhabdomyolysis. We report a rare case of rhabdomyolysis in a 24 years old pregnant woman due to hyperemesis gravidarum. She had a profound weakness. Physical examination and laboratory findings showed a need for the hospital admission. Aggressive rehydration and electrolytes were the definite treatment. Her serum creatinine kinase (CK) concentration during entry was 80,01 units/L. Continuous rehydration led to complete recovery clinically. On discharge, she had normal laboratories.